The relation between HbA1c variability and diabetic autonomic neuropathy among type-2 diabetic patients - Hossain, Md Azad; Sarkar, Mukul Kumar; Mahbub, Imtiaj; Islam, SM Shahinul (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Diabetic autonomic neuropathy (DAN) is the most neglected major and widespread microvascular complication of type-2 diabetes mellitus, involving multiple body organs. DAN is a subtype of diabetic peripheral neuropathy. Objective: To investigate the relationship between the variability of HbA1c and diabetic autonomic neuropathy in type-2 diabetes patients. Materials and methods: This study recruited a total of 150 type-2 diabetic patients to screen for diabetic autonomic neuropathy and estimated quarterly levels of HbA1c were performed within the year before enrollment. With a noninvasive procedure, DAN was validated by careful history taking, anthropometric assessment, clinical manifestations and neurological assessment. Results: Out of 150 type- 2 diabetic patients, recruited randomly, where 81 were female and 69 were male. Among all patients 29 (19.33%) had been screened positive for DAN which showed higher HbA1c than non-DAN patients. Different autonomic neuropathic dysfunction among total diabetic patients were also studies and found that the highest prevalence of sexual dysfunction among all autonomic dysfunction prevalence which is 16.66% whereas the lowest prevalence was postural hypotension that is 6.66%. The second higher prevalence is urinary incontinence (10.66%). Abnormal sweating (9.33%) and nocturnal diarrheas (7.33%) are in third and fourth position respectively. No significant (p>0.05) differences were found in the case of BMI, sex, systolic, and diastolic blood pressure between DAN and non-DAN. Data shows a major (p<0.05) risk factor for DAN has also been the prolonged period of diabetes and older age. Conclusion: The study indicates that the increased level of HbA1c in type-2 diabetic patients is closely correlated with DAN and may be considered a potent predictor of DAN in the recruited patients. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 89-95